Hypocalcemia in the Critically Ill Pediatric Patients: A Review (Dhaka Shishu (Children) Hospital Journal, 2020)
Hypocalcemia is common in the critically ill pediatric patients. However, the diagnosis of hypocalcemia in this population is complicated by interpretation of the total plasma calcium concentration. These limitations are principally the result of the effects of hypoalbuminemia and disorders of acid-base balance on the total calcium concentration. Thus, measurement of ionized calcium can be critical in determining an individual’s true serum calcium status. In this review, we first described the regulation of normal calcium metabolism and then focus on the various etiologies of hypocalcemia, which are encountered in the pediatric critical care settings. The approach to the treatment of hypocalcemia and the current consensus on treatment of hypocalcemia in the critically ill pediatric patient is also presented.DS (Child) H J 2019; 35(2) : 156-161